Integrated solar powered fan and lighting system - Mohd Nafis, Nur Nylam Balqis; Omar, Mastura; Muhd Farid, Muhammad Mursyid Akma (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Integrated Solar-Powered Fan and Lightning System is an innovative solution designed to address the challenges of unstable power supply by utilizing solar energy to ensure uninterrupted operation. This multipurpose device features a fan and LED lamp powered by a rechargeable battery charged via a solar panel. Its smart features include an LDR that turns the LED lamp on in the dark and off in bright environments, ultrasonic sensors to activate the fan when humans are detected, and a DHT22 temperature sensor that adjusts the fan speed based on the surrounding temperature. Additionally, the ESP32 module with Wi-Fi connectivity enables users to control lamp brightness and monitor real-time temperature and humidity data through the Blynk IoT app. By combining renewable energy, sensor automation, and IoT technology, this device promotes eco-friendly practices and provides a sustainable solution for both indoor and outdoor use.